Analysis of Determining Cost of Production in the Sangkar Perkutut UD Galery Sangkar Mas in Dawuhan Mangli Village, Sukowono Subdistrict, Jember Regency - Rohman, Muhammad Wahyu Lailur; Yulinartati, Yulinartati; Afroh , Ibna Kamelia Fiel (Westscience Press, 2024)
A company is an organization that operates with the aim of generating profits, by selling products (goods and/or services) to its customers. The cost of production is all costs related to the product or goods obtained, in which there are elements of product costs in the form of raw material costs, direct labor costs, and factory overhead costs. The selling price is the amount of compensation (money or goods) required to obtain a combination of goods or services. The method used is qualitative data and quantitative data. Calculation of the cost of production using the variable costing method. Calculation of Turtledove Cage Gallery UD. Sangkar Mas is the highest for 250 bird cages are the cost of production in January 2024.